Assessment of Bank Health Level towards Profit Growth - Antyo Pracoyo; Dita Putriyanti (Jurnal Ilmu Manajemen & Ekonomika, 2016)
The objective of this research is to analyze the influence of Risk Based Bank Rating (RBBR) components to growth profit banking industry in Indonesia. The sample consists of Banks which categorized as Bank Umum Kegiatan Usaha (BUKU) 4 or Banks with capital asset over 30 billion IDR. The data gathered include the period of 2011 until 2013. Technique of analysis used for this research is multiple linier regression. This research has been analyzed with EViews 7.1 program, and during the significance test it indicated that fixed effect was the most appropriate method. The result of this research shows that Non Performing Loan have a negative and significant effect to growth profit. Loan to Deposit Ratio, Good Corporate Governance, Net Interest Margin, Capital Adequacy Ratio have a positive but no significant effect to growth profit.